2012
DOI: 10.1253/circj.cj-12-0360
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Left Ventricular Vortex Flow Patterns in Association With Left Ventricular Apical Thrombus Formation in Patients With Anterior Myocardial Infarction

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp eft ventricular (LV) apical thrombus formation is a major complication in patients with LV dysfunction following an anterior myocardial infarction (MI). 1-10 Although the mechanisms of potential thrombus formation are diverse, abnormalities in apical contraction and the resulting change in the dynamics of flow leading to stagnant flow of the LV apex is one of the most important factors for thrombus formation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 21 publications
(16 reference statements)
2
46
0
Order By: Relevance
“…20 Recently, a clinical study, performed by echo-PIV, analyzed the risk of thrombus formation in patients with myocardial infarction on the anterior wall. 89 In agreement with previous results, they demonstrated that the vortex remains in a more basal location within the LV, as measured from the steady streaming flow, and this vortex characteristic is strongly associated with LV thrombus formation.…”
Section: Kinematic Aspects: Flow Transitsupporting
confidence: 92%
“…20 Recently, a clinical study, performed by echo-PIV, analyzed the risk of thrombus formation in patients with myocardial infarction on the anterior wall. 89 In agreement with previous results, they demonstrated that the vortex remains in a more basal location within the LV, as measured from the steady streaming flow, and this vortex characteristic is strongly associated with LV thrombus formation.…”
Section: Kinematic Aspects: Flow Transitsupporting
confidence: 92%
“…[25][26][27] However, this technique is available only in the 2D mode of TTE, is difficult to use in the evaluation of vortex, and is limited in terms of sub-optical images in patients with obesity or emphysema. 4D-Flow can clearly and non-invasively measure all 3D components of the vectors of blood velocity relative to all 4 spatio-temporal dimensions of the heart and great vessels, which has otherwise been difficult in TTE.…”
Section: Imaging Of the Intra-la Vortex With 4d-flowmentioning
confidence: 99%
“…Stratification of patients at risk for LVT formation is currently based primarily on a global assessment of ventricular function and image-based assessment of ventricular wall motion to identify LV regional wall akinesia and dyskinesia. Some previous studies have, however, shown that global parameters, such as EF, SV, and EDV, do not always correlate well with LVT formation (29,40,45), and existing approaches for stratifying LVT risk, therefore, lack sensitivity and specificity (44). The identification of high-risk patients and the pharmacological prevention of LVT formation are the key to preventing embolic events.…”
Section: A Computational Methods That Simultaneously Resolves the Leftmentioning
confidence: 99%
“…However, the correlation between the flow pattern and LVT risk reported in earlier studies is rather descriptive or qualitative. A quantitative metric related to the flow pattern in the LV and its correlation to LVT formation has been suggested (40), but the limitation of this prior study was that the flow patterns in LVT cases were assessed after thrombus formation, making it difficult to determine whether the metric represents conditions conducive to the genesis of LVT or the effect of the LVT on the LV flow.…”
Section: A Computational Methods That Simultaneously Resolves the Leftmentioning
confidence: 99%
See 1 more Smart Citation